Bcl-2 but not FOXP1, is an adverse risk factor in immunochemotherapy-treated non-germinal center diffuse large B-cell lymphomas. - Nyman, H; Jerkeman, M; Karjalainen-Lindsberg, M; Banham, A; Enblad, G; Leppä, S (2009)
OBJECTIVES: Non-germinal center (non-GC) phenotype, high level expression of the transcription factor forkhead box protein P1 (FOXP1) and anti-apoptotic protein Bcl-2 have been identified as unfavorable prognostic factors for diffuse large B-cell lymphoma (DLBCL) patients treated with chemotherapy. Our aim was to re-evaluate the prognostic impact of these biologic factors on the survival of the patients treated with immunochemotherapy. METHODS: Expression of Bcl-2 and FOXP1, and cell of origin based on the Hans algorithm were determined immunohistochemically from samples of 117 de novo DLBCL patients treated with R-CHOP and R-CHOEP regimens, and correlated with clinical data. RESULTS: Consistent with our previous studies, no significant difference in 2-yr survival rates between the GC- and non-GC phenotypes was found. Both FOXP1 and Bcl-2 expression were associated with the non-GC phenotype. For all patients, no prognostic impact of FOXP1 positivity on survival was observed. However, Bcl-2 negative patients had a better survival as compared to Bcl-2 positive patients [failure free survival (FFS) 97% vs. 71%, P = 0.001 and overall survival (OS) 97% vs. 82%, P = 0.034]. When Bcl-2 related survival was analyzed in the GC- and non-GC subgroups, a significant prognostic effect of Bcl-2 on FFS was seen only in the non-GC group of patients (positive 65% vs. negative 100%, P = 0.011). A trend for the difference in OS was also observed (positive 84% vs. negative 100%, P = 0.082). CONCLUSIONS: The data demonstrate that expression of Bcl-2 and FOXP1 is associated with the non-GC phenotype, but only Bcl-2 expression continues to be of prognostic significance in DLBCL patients treated with immunochemotherapy.